Objective Quantification of Trochlea Dysplasia: Assessment of Morphology Difference Between Control and Chronic Patellofemoral Instability Patients. Issue 4 (27th April 2017) - Voss, Andreas; Achtnich, Andrea; Sanghin, Shin; Murakami, Akin M.; Edgar, Cory
Aims and Objectives: Trochlear dysplasia is an important risk factor associated with patellofemoral instability, but it remains difficult to classify with consistency. Currently there is no objective way to quantify the dysplasia. The purpose of this study to define and quantify objectively the trochlea morphology by volume and length via computed tomography (CT). Hypothesis: A significant difference in trochlea groove volume and length is present within a cohort of patients with recurrent patellofemoral instability if compared to a control cohort of similar patients. Materials and Methods: One-hundred control patients (136 knees) were retrospectively reviewed and compared to 36 consecutive patients (72 knees) who were treated surgically for recurrent patella instability and known trochlea dysplasia based on a lateral x-ray. Trochlea morphology was analyzed from a pre-operative CT and data presented as trochlear sulcus volume trochlea length. To determine where along the trochlea length dysplasia is most variable, the trochlea length was radiographically divided into thirds, volume was quantified along that section and compared to control trochlea. Results: A significant difference in trochlea morphology exists between cohorts, volume (1.98 vs 3.77 cm3) and length (31.97 vs 34.66 mm). However, there appears to be a gender based difference in trochlea morphology. The trochlea volumetric analysis between the female cohorts (L: 2.02 cm3 vs. 2.94 cm3, R: 1.95 cm3 vs. 2.93 cm3) demonstrated significant less volume in instability patients (p<0.001). The proximal 30% of trochlea contributed the majority of dysplasia difference determined by comparing mean trochlea volume, 95% of the difference. This difference decreased in distal sections, 53% and 32% respectively. The total trochlea length did not appear to be significant (L: p=0.858, R: p=0.913). It appears dysplasia alone may not directly lead to symptoms demonstrated by trochlea volumetric comparisons within symptomatic recurrent patella instability and contralateral asymptomatic patella (p=0.274). Conclusion: The authors believe this reproducible technique can be used to quantify the trochlea morphology into measurements to be used describing the severity of the dysplasia. The data confirms that symptomatic trochlea dysplasia is a "proximal" process affecting early knee flexion contact between patella and trochlea.